A study on visual inspection of citrus sorters in a packhouse in the Eastern Cape of South Africa - Maher, Christopher Richard (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics)
Background and Purpose. The South African citrus industry is a major global producer of citrus as well as the second largest exporter of citrus fruit in the world. This industry provides employment to an estimated 112 000 workers in South Africa and is vital in providing economic opportunities to communities such as those in the Sunday's River Valley in the Eastern Cape province of South Africa due to the low employment and education levels within this province. Citrus sorting is a visual inspection task that requires workers to sustain attention and remain vigilant for the duration of a working shift. Their role in the packhouse is to ensure that no defective products are packed for export or the local market and that the fruit meets the customers' expectations. Since the demands of sorting citrus are poorly understood, this study attempted to assess the effect that sorting citrus has on vigilance performance as well as attempt to quantify perceived workload while taking into account different contextual factors that affect perceptions of this working task. Methods. This study was conducted within a citrus packhouse in the Eastern Cape province of South Africa. The sample was comprised of individuals employed by the packhouse as citrus sorters. In addition to a recruitment and information session, testing was conducted at three intervals during a working shift on four consecutive days. Each time, indicators of vigilance, such as correct responses, sensitivity, reaction time, false alarms and misses, were collected during a 5-minute computerised version of the Mackworth Clock-test, while perceived workload was assessed with the NASA-TLX scale, and sleepiness was recording using the WITS Sleepiness Scale. Furthermore, an open-ended question was asked to further understand factors affecting the ability of participants to concentrate during their task of sorting. Results. 18 participants consented to participate in this study. 16 of these individuals identified as female with an average age of 30 years (Â± 7). 83% of participants were of Black African descent and were isiXhosa speakers, while 17% of participants were of Coloured descent and Afrikaans speakers. This study found that performance, as measured by the percentage of correct responses, sensitivity and reaction time on the 5-minute long Mackworth Clock Test was not significantly affected as time-on-task for sorting citrus increased during a working shift, neither did performance on the vigilance test change as days of the week proceeded. However, 'misses' during the vigilance test were found to significantly decrease over the course of a working shift, thus contradicting the expected outcomes of this study. Perceived workload of sorting citrus, as well as perceived sleepiness, significantly increased with time-on-task during the course of a working shift. The major contributions for this increase in perceived workload while sorting citrus were derived from the Mental Demand and Physical Demand sub-scale for the NASA-TLX. However, responses from the open-ended question indicated that participants generally enjoyed their work, although there were factors, such as the nature of fruit and social set-up of work, that negatively affected this perception. Discussion. The results from this study contradicted the researcher's expectations. It was anticipated that measures of correct responses and sensitivity would decrease and misses, and reaction time would increase with time-on-task for sorting citrus, yet vigilance indicators from the Mackworth Clock Test generally indicated no change in vigilance, and, according to "misses" even improved with time-on-task. A likely explanation for this is that the use of a 5-minute Mackworth Clock-test was unsuitable in this context, or rather, the time of this test was not long enough to induce a 'vigilance decrement'. Furthermore, in order to administer this vigilance test, participants were taken off the production line and led to a testing room which most likely increased their levels of arousal, thus affecting performance on the vigilance test. However, even though perceived sleepiness was found to significantly increase over the course of a working shift, these data correlated poorly with the vigilance results, thus contradicting the expected outcomes of the study. Mental demand significantly increased, possibly due to the demand of attentional informational processing required for sorting, as well as various environmental factors present within the packhouse. Physical demand, too, significantly increased as workers were required to remain standing throughout their working task as well as to make use of their upper extremities to remove defective fruit. Correlation analyses showed significantly weak correlation for Mackworth Clock Test variables and sleepiness ratings to all other variables. NASA-TLX variables, however, generally showed significantly moderate correlations with one another. Conclusion. It remains unclear how vigilance changes and sustained attention while sorting citrus, since the experiment did not show changes in performance. This is largely attributed to the methodological set-up which could have increased arousal and therefore affected vigilance. It is recommended that future studies research vigilance and sustained attention during the sorting itself, rather than attempting to infer vigilance results from a computerised vigilance test. Perceived workload of sorting, however, increased over the course of a working shift due to significant increases in perceptions of the physical and mental demands of sorting. Future studies should address concerns relating to the physical demand of sorting. Furthermore, it would be beneficial to compare responses of day and night shift sorters to further understand how the relationship between these variables may change.
Keywords: Citrus fruit industry -- South Africa -- Eastern Cape; Packing-house workers; Fatigue in the workplace; Drowsiness; Visual inspection; Employees Workload